Divided environments an international political ecology of climate change, water and security - Selby, Jan 1972-; Daoust, Gabrielle 1984-; Hoffmann, Clemens 1978- (Cambridge University Press, 2022)
What are the implications of climate change for twenty-first-century conflict and security? Rising temperatures, it is often said, will bring increased drought, more famine, heightened social vulnerability, and large-scale political and violent conflict; indeed, many claim that this future is already with us. Divided Environments, however, shows that this is mistaken. Focusing especially on the links between climate change, water and security, and drawing on detailed evidence from Israel-Palestine, Syria, Sudan and elsewhere, it shows both that mainstream environmental security narratives are misleading, and that the actual security implications of climate change are very different from how they are often imagined. Addressing themes as wide-ranging as the politics of droughts, the contradictions of capitalist development and the role of racism in environmental change, while simultaneously articulating an original 'international political ecology' approach to the study of socio-environmental conflicts, Divided Environments offers a new and important interpretation of our planetary future